RETRACTED: Atorvastatin May Attenuate Recurrence of Chronic Subdural Hematoma - Liu, Hua; Luo, Zhengxiang; Liu, Zhongkun; Yang, Jian; Kan, Shifeng (Frontiers in Neuroscience, 2016)
Objective: Chronic subdural hematoma (CSDH) is a common form of intracranial hemorrhage with a substantial recurrence rate. Atorvastatin may reduce CSDH via its anti-inflammatory and pro-angiogenesis effects, but its effectiveness for preventing recurrent CSDH has never been explored. We hypothesized that atorvastatin is effective in reducing recurrence of CSDH after surgery and identified determining factors predictive of hematoma recurrence. Methods: A prospective study was conducted in 168 surgical cases of CSDH.All patients were randomly assigned to the group treated with atorvastatin or control group. Clinically relevant data were compared between two groups, and subsequently between the recurrence and non-recurrence patients. Multiple logistic regression analysis of the relationship between atorvastatin treatment and the recurrence using brain atrophy, septated and bilateral hematoma was performed. Results: Atorvastatin group conferred an advantage by significantly decreasing the recurrence rate (P = 0.023), and patients managed with atorvastatin also had a longer time-to-recurrence (P = 0.038). Admission brain atrophy and bilateral hematoma differed significantly between the recurrence and non-recurrence patients (P = 0.047 and P = 0.045). The results of logistic regression analysis showed that atorvastatin significantly reduced the probability of recurrence; severe brain atrophy and bilateral hematoma were independent risk factors for recurrent CSDH. Conclusions: Atorvastatin administration may decrease the risks of recurrence.Patients with severe brain atrophy and bilateral CSDH are prone to the recurrence.